2012
DOI: 10.15376/biores.7.4.5469-5477
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Thermal, and Mechanical Properties of Starch Biocomposite Films Reinforced by Cellulose Nanocrystals From Rice Husks

Abstract: A series of glycerol-plasticized starch composites reinforced by rice-husk cellulose nanocrystals was successfully fabricated through the solution casting technique. The rice husks must undergo alkali treatment, bleaching, and sulphuric acid hydrolysis before cellulose nanocrystals can be produced. The cellulose nanocrystal content used as filler was varied from 0 to 10 wt%. The thermal stability of the composite were analysed by thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG). The starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…TS was reduced basically due to the agglomeration of nanofillers in the seaweed matrix, which caused filler-filler interaction instead of fillermatrix interaction (Johar and Ahmad 2012). Therefore, it was believed that the poor filler-matrix interfacial interaction was formed in this case.…”
Section: Mechanical Properties Of Bio-nanocomposite Filmsmentioning
confidence: 91%
“…TS was reduced basically due to the agglomeration of nanofillers in the seaweed matrix, which caused filler-filler interaction instead of fillermatrix interaction (Johar and Ahmad 2012). Therefore, it was believed that the poor filler-matrix interfacial interaction was formed in this case.…”
Section: Mechanical Properties Of Bio-nanocomposite Filmsmentioning
confidence: 91%
“…The cellulose fibers were isolated according to Johar and Ahamad, with some modifications. The cellulose fibers were dried in an oven with air circulation (400‐6ND; Nova Ética, São Paulo, Brazil) at 50 °C for 24 h and stored in a sealed container.…”
Section: Methodsmentioning
confidence: 99%
“…Research efforts in the area of polymeric materials have focused on the development of biodegradable materials obtained from renewable resources . Among these materials the starches that are the most abundant and the cheapest materials that come from renewable resources stand out.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of CNCs improves the thermomechanical properties and reduces the water sensitivity of starch-based nanocomposites. It has been reported that CNCs derived from rice husk increase the Young's modulus and tensile strength of thermoplastic starch films due to the strong interactions between the starch matrix and the high aspect ratio nanofibers (Abdul Khalil et al 2012;Johar and Ahmad 2012). Khan et al (2012), who investigated CNC-reinforced chitosan-based biodegradable films, found that the tensile strength of the nanocomposite films with 5% (w/w) CNC content was optimum and 26% higher than that of the control chitosan films.…”
Section: Introductionmentioning
confidence: 99%